The pungent substances piperine, capsaicin, 6-gingerol and polygodial inhibit the human two-pore domain potassium channels TASK-1, TASK-3 and TRESK - Leopoldo Raul Beltran; Corinna eDawid; Madeline eBeltran; Guenter eGisselmann; Katharina eDegenhardt; Klaus eMathie; Thomas eHofmann; Hanns eHatt (Frontiers Media S.A., 2013)
For a long time, the focus of trigeminal chemoperception has rested almost exclusively on TRP channels. However, two-pore domain (K2P) potassium channels have recently been identified as targets for substances associated with typical trigeminal sensations, such as numbing and tingling. In addition, they have been shown to be modulated by several TRP agonists. We investigated whether the pungent substances piperine, capsaicin, 6-gingerol and polygodial have an effect on human K2P channels. For this purpose, we evaluated the effects of these pungent substances on both wild-type and mutant K2P channels by means of two-electrode voltage-clamp experiments using Xenopus laevis oocytes. All four pungent substances were found to inhibit the basal activity of TASK-1 (K2P 3.1), TASK-3 (K2P 9.1), and TRESK (K2P 18.1) channels. This inhibitory effect was dose-dependent and, with the exception of polygodial on TASK-1, fully reversible. However, only piperine exhibited an IC50 similar to its reported EC50 on TRP channels. Finally, we observed for TASK-3 that mutating H98 to E markedly decreases the inhibition induced by piperine, capsaicin, and 6-gingerol, but not by polygodial. Our data contribute to the relatively sparse knowledge concerning the pharmacology of K2P channels and also raise the question of whether K2P channels could be involved in the pungency perception of piperine.